Complete asymptotic decomposition of the sojourn probability of a diffusion process in thin domains with moving boundaries - Gasanenko, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We investigate a diffusion process ξ(t) with absorption defined in a thin domainD ε ={(x,t)∶εG 1 (t)